THE MADINAH CHARTER AND RELIGIOUS MODERATION: THE LINK, STRATEGIES, AND METHODS FOR EFFECTIVE IMPLEMENTATION IN MADRASAH - Pramitha, Devi; Nikmah, Faridatun; Anggarini, Ida Fitri; Noviyanti, Shobihatul Fitroh (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
The Madinah Charter stands as Islam's fundamental law, encompassing principles such as tolerance, the rule of law, humanism, and societal norms. These principles align closely with the values upheld in religious moderation, a concept prevalent in contemporary media. This study aimed to elucidate the intersections between the Madinah Charter's principles and the implementation of religious moderation strategies within Madrasahs. Conducted in two specific Madrasahs in Malang, this comprehensive investigation involved six students and two Islamic history instructors as data sources. 1) Analysis of the data revealed a significant correlation between the Madinah Charter and religious moderation. 2) Teachers employed diverse methodologies and tactics to translate the ideals of the Madinah Charter and religious moderation into practical application. The research highlights the pivotal role of Madrasahs as key platforms for instilling the values of the Madinah Charter and religious moderation, serving as a preventive measure against extremism among students